Hadith #3504 - Sahih Muslim - Abu Qilaba (Sahih Muslim)
It is the Sunnah to stay with a virgin (after having married her) for a week. Khalid (one of the narrators) said: If wish I can say that it can be traced up to the Prophet (ﷺ).
Grade: Sahih

Hadith #3932 - Sahih Muslim - Abu Qilaba (Sahih Muslim)
I was in Syria (having) a circle (of friends). in which was Muslim b. Yasir. There came Abu’l-Ash’ath. He (the narrator) said that they (the friends) called him: Abu’l-Ash’ath, Abu’l-Ash’ath, and he sat down. I said to him: Narrate to our brother the hadith of Ubada b. Samit. He said: Yes. We went out on an expedition, Mu’awiya being the leader of the people, and we gained a lot of spoils of war. And there was one silver utensil in what we took as spoils. Mu’awiya ordered a perso
Grade: Sahih

Hadith #4226 - Sahih Muslim - Abu Qilaba (Sahih Muslim)
I was sitting behind ‘Umar b. ‘Abd al-‘Aziz and he said to the people: What do you say about al-Qasama? Thereupon ‘Anbasa said: Anas b Malik narrated to us such and such (hadith pertaining to al-Qasama). I said: This is what Anas had narrated to me: People came to Allah’s Apostle (ﷺ), and the rest of the hadith is the same. When I (Abu Qilaba) finished (the narration of this hadith), ‘Anbasa said: Hallowed be Allah. I said: Do you blame me (for telling a lie)? He (‘Anbasa) said:
Grade: Sahih